(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The goal of this study is to determine physicochemical characteristics of the effluent of the municipal slaughter-house of the Maradi city and to recommend a suitable treatment allowing it’s recycling, thus reducing the harmful effect which undergoes the receiving environment. The experimental results obtained showed that average values of pH, temperature, turbidity and conductivity are respectively of 7.3, 26.6°C, 326 NTU and 4720 µs/cm. Average concentrations in phosphorus, phosphate, nitrite, nitrate, calcium, calcium carbonate, magnesium, iron, fluor and organic matter, in milligram per liter, are: 0.73, 2.23, 1.7, 211.64, 148.33, 8.53, 42, 9.24, 0.15, 32.08 and 426.67, respectively.